2003
DOI: 10.1086/375843
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus (CMV) and Human Immunodeficiency Virus (HIV) Burden, CMV End-Organ Disease, and Survival in Subjects with Advanced HIV Infection (AIDS Clinical Trials Group Protocol 360)

Abstract: We undertook a prospective study to analyze cytomegalovirus (CMV) end-organ disease (EOD) in subjects with advanced human immunodeficiency virus (HIV) infection. Of 403 individuals without prior CMV EOD who were followed up for a median of 151 weeks, 56 died and 21 developed CMV EOD. Twenty of the subjects with CMV EOD had CD4 cell counts of < or =50 cells/mm3 and HIV RNA level of >10,000 copies/mL of plasma at baseline; in these 20 subjects, an increase of CMV DNA level to greater than the quantification limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
1
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 25 publications
3
43
1
7
Order By: Relevance
“…HIV-specific CD4 ϩ T cells that produced IL-2 did have levels of PD-1 similar to those of IFN-␥-producing CMV-specific CD4 ϩ T cells, suggesting that even the less mature IL-2-producing HIV-specific CD4 ϩ T cells are somewhat impaired. In addition, we did see higher expression of PD-1 on CMV-specific CD4 ϩ T cells in HIV-infected subjects than in HIV-seronegative subjects, which may reflect the higher level of CMV reactivation documented in subjects with active HIV disease (30,31).…”
Section: Discussionmentioning
confidence: 61%
“…HIV-specific CD4 ϩ T cells that produced IL-2 did have levels of PD-1 similar to those of IFN-␥-producing CMV-specific CD4 ϩ T cells, suggesting that even the less mature IL-2-producing HIV-specific CD4 ϩ T cells are somewhat impaired. In addition, we did see higher expression of PD-1 on CMV-specific CD4 ϩ T cells in HIV-infected subjects than in HIV-seronegative subjects, which may reflect the higher level of CMV reactivation documented in subjects with active HIV disease (30,31).…”
Section: Discussionmentioning
confidence: 61%
“…For HIV-positive patients with low CD4 counts, Erice et al studied the use of a CMV antigen assay (limit of detection reported as 200 copies/ml) and the reference protocol used in our study (11). In univariate analysis after adjustment for HIV load and CD4 count, an increase in the CMV copy number to Ͼ200/ml during the study was significantly associated with decreased survival.…”
Section: Discussionmentioning
confidence: 90%
“…Initial reports have demonstrated a broad linear range and a lower limit of detection below that of the COBAS CMV Monitor assay (4). While copy numbers of CMV DNA as low as those detected with the artus assay have been reported, the clinical significance of these "low-positive" levels in a population of immune-suppressed patients has not been well described (3,11,15).…”
mentioning
confidence: 99%
“…Este patrón es concordante con lo descrito previamente 11 . Aunque infrecuente, la neumonía por CMV ha sido reportada en pacientes con infección por VIH/SIDA y asociada como en este caso a un mal pronóstico 15 . Las infecciones mixtas, siempre con un compromiso pulmonar asociado y las neurológicas, ocuparon un papel importante dentro de las infecciones.…”
Section: Artículo Originalunclassified